If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 = 6 + -2z Solving 2 = 6 + -2z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '2z' to each side of the equation. 2 + 2z = 6 + -2z + 2z Combine like terms: -2z + 2z = 0 2 + 2z = 6 + 0 2 + 2z = 6 Add '-2' to each side of the equation. 2 + -2 + 2z = 6 + -2 Combine like terms: 2 + -2 = 0 0 + 2z = 6 + -2 2z = 6 + -2 Combine like terms: 6 + -2 = 4 2z = 4 Divide each side by '2'. z = 2 Simplifying z = 2
| b^3-b^2-56b=0 | | 36u=576 | | 4x-8/x-2 | | 2*(10+g)= | | 3x=5(25-7) | | 10x+15y=4290 | | 5X-8=-88 | | 2x-x+10=5x-2 | | 14-8c=352 | | (4n-20)=(2n+20)+n | | 3x=5(10-7) | | 2*5x=40 | | H/3=50 | | -22-x=12 | | 0=-16t^2+100t+15 | | 5x-4-5x=1 | | Y(9/5)x-8 | | 6x+3x+8=17 | | -33=-3+5y | | 3/8=n/30 | | Y-6=(3/4)(X-0) | | 4(y-6)=.8 | | -2z+3-z=-z-4(z+2) | | -8d=96 | | 4(y-3)=.8 | | x/y-z=a | | 11+5a=1 | | 10x-10=6x+10 | | 4(.2-3x)=.8 | | y+x+40=180 | | -24+m=-11 | | 3x+13+5x-5+2x+2=180 |